2019
DOI: 10.4197/met.28-1.9
|View full text |Cite
|
Sign up to set email alerts
|

Causes of Occupational Accidents and Injuries in Construction Industry in Jeddah City

Abstract: This study identified the causes of accidents and injuries in the construction industry among 300 workers in Jeddah City, situated on the coast of the Red Sea of Saudi Arabia. Results from the questionnaire showed that the major cause of accidents and injuries is the lack of awareness about occupational safety and lack of experience among the workers (> 82%); and the most common type of accidents and injuries that occur in the construction industry, are workers falling from a height (>80%), and electrica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…The existing literature on construction safety in Saudi Arabia also confirms the menace of FFH accidents [8,9]. Strikingly, Abukhashabah et al [10] reported that FFH consists of 80% of the accidents in the construction sector in the city of Jeddah in Saudi Arabia. Hence, the need to understand, and consequently control the rate of FFH accidents in Saudi Arabia is obvious.…”
mentioning
confidence: 75%
“…The existing literature on construction safety in Saudi Arabia also confirms the menace of FFH accidents [8,9]. Strikingly, Abukhashabah et al [10] reported that FFH consists of 80% of the accidents in the construction sector in the city of Jeddah in Saudi Arabia. Hence, the need to understand, and consequently control the rate of FFH accidents in Saudi Arabia is obvious.…”
mentioning
confidence: 75%
“…To measure the sensitivity of a model, we use recall. Recall tells us how many TP observations the model detected correctly; see Equation (3). The mean average precision (mAP) is used to measure the accuracy of the object detection model across all classes in a given dataset, as shown in Equation ( 4), where AP is the average of all precisions (see Equation ( 5)), and n is the total number of classes [22].…”
Section: Testing and Evaluationmentioning
confidence: 99%
“…Construction sites are known to be highly hazardous environments due to their dynamic and temporary nature. Some studies showed that accidents at construction sites can be caused by many factors, as follows [2,3]: lack of awareness and experience among workers, lack of safety training among workers, workers not wearing personal protective equipment (PPE), no safety officer located in danger zones and machinery defects and errors. Construction workers are involved in many activities that might expose them to risks and accidents.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been determined that the main factors of happening these accidents can be found human errors, unsafe behavior, a lack of knowledge and safety training, and poor and ineffective management at the sites (Abukhashabah et al 2019;Bussier and Chong 2022;Namian et al 2022b). One of the accident prevention methods is identifying, evaluating, and controlling potential dangers (Christian et al 2009).…”
Section: Epic Series In Built Environmentmentioning
confidence: 99%